The Implementation of Open and Distance Education to Advance Educational Access in Remote Areas - Yasir Riady; Melisa Arisanty; Eko Kuswanti; Sri Sukatmi; Muhammad Firman Karim; Muhammad Ajmal (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: Indonesia, an archipelagic nation comprising over 17,000 islands, encounters ongoing difficulties in providing equitable access to quality education throughout its many areas.Aims: This study investigates the implementation of Open and Distance Education (ODE) as a crucial approach for enhancing educational accessibility in isolated regions. Through the application of digital technologies and adaptable learning frameworks, ODE surmounts geographical, economic, and infrastructural obstacles that frequently constrain conventional educationMethods: ODE allows learners to obtain quality education irrespective of their geographical location, promoting inclusion and opportunities for lifelong learning. This study employed qualitative methods to investigate and analyze educational access in rural regionsResults: The efficacy of ODE is contingent upon several crucial aspects, including internet connectivity, digital literacy, and governmental assistance in policy and infrastructure development. Addressing these obstacles will guarantee that ODE evolves into a lasting solution for enhancing educational equity and empowering communities in remote areas.Conclusion: Open and Distance Education has demonstrated its efficacy in broadening educational access, particularly in isolated regions. The adoption of distance education enables students to learn at their own pace and under their own circumstances, without dependence on traditional educational infrastructure, which is frequently limited in remote areas. This strategy also enables educators to engage a greater number of pupils using more efficient resources.